Hands-On Concurrency with Rust : Confidently build memory-safe, parallel, and efficient software in Rust. - L. Troutwine, Brian (Packt Publishing, 2018)
Writing safe and correct parallel programs is tough. Reasoning about concurrent memory modification is tough; efficiently exploiting the modern computing environment (with its multi-layered caches and deep execution pipelines) is also tough. Most systems programming languages add a further complication: unsafe memory access. The burden on you ...